L’io dissolto. Tracce di Baudelaire in Gadda - Francesco Rivelli (Parole Rubate, 2011)
The relationship between Gadda and Baudelaire originates from an autobiographical identification which immediately leads to a wider ethical reflection on self-consistency. This article thus reconstructs the textual affinities between the two authors to show how the polarities which trap the subject on the edge of dissolution are already present in Les Fleurs du mal and constitute a model for Gadda.